Penerapan Model Discovery Learning Berbantuan Permainan Ular Tangga untuk Meningkatkan Pemahaman Konsep Matematis Peserta Didik Kelas IX-4 UPT SMP Negeri 8 Medan - Hutagalung, Tia Basana; Siregar, Rosliana; Ramli, Amalia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This Classroom Action Research aims to improve students' ability to understand mathematical concepts through the application of the Discovery Learning model supported by snake and ladder games. The research subjects consisted of 29 students. The instruments used in this study include observation sheets, written tests, and documentation. The data obtained was analyzed through several processes, namely data reduction, data presentation, and drawing conclusions. The success of the mathematical concept comprehension test in this study is determined by two criteria, namely the average score of the mathematical concept comprehension test results and the percentage of students who achieve a minimum completeness score. The average score of the mathematical concept comprehension test results in cycle I and cycle II was 67.5 and 78.5 respectively. The percentage of students who completed the first and second cycles were 65.5% and 80.1% respectively. This shows that in the second cycle, the average score of the mathematical concept comprehension test results and the percentage of students who completed it have met the set criteria. Thus, the application of the Discovery Learning model supported by the snake and ladder game has proven successful in an effort to improve the ability to understand mathematical concepts of students in grades IX-4 of UPT SMP Negeri 8 Medan